2004
DOI: 10.1093/hmg/ddh124
|View full text |Cite
|
Sign up to set email alerts
|

Foxl2 disruption causes mouse ovarian failure by pervasive blockage of follicle development

Abstract: FOXL2 mutations cause gonadal dysgenesis or premature ovarian failure (POF) in women, as well as eyelid/forehead dysmorphology in both sexes (the 'blepharophimosis-ptosis-epicanthus inversus syndrome', BPES). Here we report that mice lacking Foxl2 recapitulate relevant features of human BPES: males and females are small and show distinctive craniofacial morphology with upper eyelids absent. Furthermore, in mice as in humans, sterility is confined to females. Features of Foxl2 null animals point toward a new me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
388
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(412 citation statements)
references
References 32 publications
14
388
0
10
Order By: Relevance
“…[19,20] XY homozygous animals do not display any defect in testis development and XX Foxl2 À/À mice are phenotypically female, but sterile. [19,20] Indeed, ovaries of KO mice are small, severely disorganized, and primordial Follicles either do not form or do not proceed to further maturation stages. [19,20] Interestingly, germ cells of neither Foxl2 KO mice model seem to be affected during early folliculogenesis.…”
Section: Foxl2: a Molecular Actor In The Spotlightmentioning
confidence: 97%
“…[19,20] XY homozygous animals do not display any defect in testis development and XX Foxl2 À/À mice are phenotypically female, but sterile. [19,20] Indeed, ovaries of KO mice are small, severely disorganized, and primordial Follicles either do not form or do not proceed to further maturation stages. [19,20] Interestingly, germ cells of neither Foxl2 KO mice model seem to be affected during early folliculogenesis.…”
Section: Foxl2: a Molecular Actor In The Spotlightmentioning
confidence: 97%
“…Besides MAP3K1, embryonic eyelid closure depends on signals derived from WNT, Sonic hedgehog, BMP/Activin, FGF and EGF (Luetteke et al, 1993;Mine et al, 2005;Gage et al, 2008;Huang et al, 2009). In addition, eyelid closure requires the participation of a number of intracellular signaling kinases, such as JNK, ROCK and CDH1, and nuclear transcription factors, such as c-Jun, Fra-2, FOXL2, SMAD and GRHL3 (McHenry et al, 1998;Li et al, 2003;Zenz et al, 2003;Zhang et al, 2003;Uda et al, 2004;Thumkeo et al, 2005;Takatori et al, 2008;Yu et al, 2008;Naoe et al, 2010). While how these factors are organized into a morphogenetic network for eyelid closure has not been well understood, molecular analyses of these mice have begun to unveil that some of the factors are organized into concerted signal transduction cascades.…”
Section: Map3k1 In Ocular Surface Developmentmentioning
confidence: 99%
“…Although in early development, cFoxL2 seems to play a role in the activation and maintenance of aromatase expression, its function in adult ovaries needs to be elucidated. Recent studies on FoxL2 null mice demonstrated that FoxL2 is crucial for primordial follicle formation (Uda et al, 2004;Schmidt et al, 2004). The presence of cFoxL2 expression in the pregranulosa cells of primordial follicles at D14 suggests that cFoxL2 may have similar role in the chicken ovary.…”
Section: Foxl2 and Later Developmentmentioning
confidence: 99%